PENERAPAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA PEMBELARAN TEMATIK POKOK BAHASAN SIKLUS AIR - Salamah, Ummu; Ubaidillah, Aan Fardani (INCARE, International Journal of Educational Resources, 2020)
This study aims to improve students' understanding of thematic subjects Theme 8 Sub-theme 1 learning 2 Subjects the Water Cycle through the application of the Contextual Teaching and Learning method. Understanding is how a person maintains, differentiates, suspects, explains, expands, concludes, generalizes, provides examples, rewrites, and estimates. Understanding can be seen and measured by seeing the extent to which students can explain an event or material using their own language. This research method uses Classroom Action Research (CAR) which is integrated simultaneously, with a Quantitative Approach approach. This type of research used in this research is a critical study. The results showed that through the application of the Contextual Teaching and Learning method was proven to increase students' understanding. In the first cycle the learning outcomes of students reached an average of 81.6%, and the percentage of completeness was 83.3%. In the second cycle the learning outcomes of students reached an average of 88.63%, the percentage of completeness was 88.8%.